Hubungan Kontrol Diri Dengan Burnout Akademik Pada Siswa Kelas XI MAN 2 Deli Serdang Tahun Ajaran 2024/2025 - Tendang, Yopa Jelita; Saragih, Nurul Azmi (Program Studi Bimbingan dan Konseling FKIP UMSU, 2025)
This study aims to determine the relationship between self-control and academic burnout in class XI students of MAN 2 Deli Serdang in the 2024/2025 academic year. This study uses a quantitative approach with a correlational method. The population in this study amounted to 430 students and the sampling technique used a simple random sampling technique of 10% of the population, namely 43 students. The data collection instrument was in the form of a self-control and academic burnout questionnaire which was compiled based on theoretical indicators and tested for validity and reliability. Based on the data analysis that has been carried out using the product moment correlation test calculation, the results of the study were obtained, namely the correlation coefficient (r) of -0.544 and significance (p) of = 0.000 (p 0.05). The results of the study state that there is a relationship between self-control and academic burnout in class XI students of MAN 2 Deli Serdang in the 2024/2025 academic year. The results of the study indicate a significant negative relationship between self-control and academic burnout in students, which means that the higher the level of student self-control, the lower the level of academic burnout they experience. Meanwhile, the coefficient of determination obtained was 27.8%, which means that the influence of self-control on academic burnout was 27.8%, while family was 72.2% influenced by other factors not examined in this study.